Performance of Karan-Fries Calves as Affected by Supplementation of Rumen Protected Methionine plus Lysine and Choline - ,, Shailesh Sai; ,, Mithilesh Chaurasiya; Thakur, S. S.; ,, N. Kewalramani; ,, Jasmine Kaur (Indian Journal of Animal Nutrition, 2018)
This study was conducted to evaluate the effect of supplementing rumen protected methionine plus lysine (RPML) and rumen protected choline (RPC) on nutrient utilization, growth performance and haematological parameters in 18 crossbred female Karan-Fries calves (age 7.4 mo; BW 94.64Â±5 kg) divided into 3 groups of 6 animals each. The animals were randomly assigned to one of the treatment groups viz. T1 (control), T2 (RPML supplement) and T3 (RPC supplement). Animals were fed a basal ration consisting of wheat straw-green fodderconcentratemixture as per requirements. The calves in group T2 were supplemented with 2 g rumen protected methionine (RPM; net 0.78 g intestinally deliverable) plus 17 g rumen protected lysine (RPL; net 3.7 g intestinally deliverable) while those in group T3 were given 27 g rumen protected choline (equivalent to 5 gcholine post ruminally) per calf per day for 90 days. The digestibility of nutrients was similar in different groupsexcept that of CP which was higher (P